2011
DOI: 10.1016/j.biopsych.2010.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate N-methyl-D-aspartate Receptor Antagonists Rapidly Reverse Behavioral and Synaptic Deficits Caused by Chronic Stress Exposure

Abstract: Background Despite widely reported clinical and preclinical studies of rapid antidepressant actions of glutamate N-methyl-D-aspartic acid (NMDA) receptor antagonists, there has been very little work examining the effects of these drugs in stress models of depression that require chronic administration of antidepressants, or the molecular mechanisms that could account for the rapid responses. Methods We used a rat 21-day chronic unpredictable stress (CUS) model to test the rapid actions of NMDA receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

83
865
5
21

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 975 publications
(974 citation statements)
references
References 48 publications
83
865
5
21
Order By: Relevance
“…Both processing speed and attention have been linked to dopamine functioning within prefrontal-subcortical circuits (Cropley et al, 2006), and ketamine is known to modulate dopamine signaling within the striatum and prefrontal cortex in animals (Moghaddam et al, 1997) and humans (Kegeles et al, 2000;Rabiner, 2007;Smith et al, 1998). Mechanistic studies in animals show that ketamine rapidly enhances synaptic plasticity at the level of prefrontal cortical neurons (Li et al, 2010(Li et al, , 2011, and is able to rapidly reverse stress-induced dendritic atrophy and behavioral depression in a brain-derived neurotrophic factor (BDNF)-dependent manner (Li et al, 2011;Liu et al, 2012). A recent study found that ketamine reversed deficit dopamine signaling in a learned helplessness model of depression and normalized synaptic plasticity within the nucleus accumbens (indexed by long-term potentiation) via activation of dopamine D1 receptors (Belujon and Grace, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both processing speed and attention have been linked to dopamine functioning within prefrontal-subcortical circuits (Cropley et al, 2006), and ketamine is known to modulate dopamine signaling within the striatum and prefrontal cortex in animals (Moghaddam et al, 1997) and humans (Kegeles et al, 2000;Rabiner, 2007;Smith et al, 1998). Mechanistic studies in animals show that ketamine rapidly enhances synaptic plasticity at the level of prefrontal cortical neurons (Li et al, 2010(Li et al, , 2011, and is able to rapidly reverse stress-induced dendritic atrophy and behavioral depression in a brain-derived neurotrophic factor (BDNF)-dependent manner (Li et al, 2011;Liu et al, 2012). A recent study found that ketamine reversed deficit dopamine signaling in a learned helplessness model of depression and normalized synaptic plasticity within the nucleus accumbens (indexed by long-term potentiation) via activation of dopamine D1 receptors (Belujon and Grace, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although deficient synaptic plasticity (LTP) is thought to underlie cognitive impairment, the delayed antidepressant effect is thought to be driven by enhanced synaptic plasticity in key brain regions implicated in MDD (Duman et al, 2012). In particular, in rodent models of chronic stress, ketamine and NR2B NAMs have been shown to activate the BDNFmTOR signaling pathways, leading to increased translation of synaptic proteins, enhanced synaptogenesis, and alleviation of depression-related behaviors (Duman et al, 2012;Li et al, 2010Li et al, , 2011. Indeed, using hippocampal LTP as a measure of plasticity it was recently reported that LTP is robustly enhanced in slice preparations taken from animals dosed 24 h previously with i.v.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the monoamine-based antidepressants, NMDAR antagonists rapidly reverse the low levels of synaptic proteins and spine loss in the medial PFC [50] . [51,52] .…”
Section: Dysfunctional Neural Plasticity In Depressionmentioning
confidence: 99%
“…A few days (~5 days) of fluoxetine administration increases synaptic density in the hippocampal CA1 pyramidal cell layer, and 14 days of treatment has similar effects in the CA3 pyramidal cell layer [48] . In the olfactory bulbectomy model of depression, chronic treatment with the tricyclic antidepressant amitriptyline blocks the stress-induced decrease in spine density in hippocampal DG, CA1, and CA3 neurons [49] .In addition to the monoamine-based antidepressants, NMDAR antagonists rapidly reverse the low levels of synaptic proteins and spine loss in the medial PFC [50] . [51,52] .…”
mentioning
confidence: 99%
See 1 more Smart Citation